Precarious Creativity: Global Media, Local Labor - Curtin, Michael; Sanson, Kevin (University of California Press, 2016)
Precarious Creativity examines the seismic changes confronting media workers in an age of globalization and corporate conglomeration. This pathbreaking anthology peeks behind the hype and supposed glamor of screen media industries to reveal the intensifying pressures and challenges workers face. The authors take on crucial issues and provide insightful case studies of workplace dynamics regarding creativity, collaboration, exploitation, and cultural difference. Furthermore, they investigate working conditions and organizing efforts on all six continents, offering comprehensive analysis of contemporary screen media labor in places such as Lagos, Prague, Hollywood, and Hyderabad, across a range of job categories that includes visual effects, production services, and adult entertainment. With contributions from John Caldwell, Vicki Mayer, Herman Gray, Tejaswini Ganti, and others, this collection offers timely critiques of media globalization and broader debates about labor, creativity, and precarity.